A conserved regulatory program initiates lateral plate mesoderm emergence across chordates - Prummel, Karin D; Hess, Christopher; Nieuwenhuize, Susan; Parker, Hugo J; Rogers, Katherine W; Kozmikova, Iryna; Racioppi, Claudia; Brombacher, Eline C; Czarkwiani, Anna; Knapp, Dunja; Burger, Sibylle; Chiavacci, Elena; et al. (Nature communications, 2019)
Cardiovascular lineages develop together with kidney, smooth muscle, and limb connective tissue progenitors from the lateral plate mesoderm (LPM). How the LPM initially emerges and how its downstream fates are molecularly interconnected remain unknown. Here, we isolate a pan-LPM enhancer in the zebrafish-specific draculin (drl) gene that provides specific LPM reporter activity from early gastrulation. In toto live imaging and lineage tracing of drl-based reporters captures the dynamic LPM emergence as lineage-restricted mesendoderm field. The drl pan-LPM enhancer responds to the transcription factors EomesoderminA, FoxH1, and MixL1 that combined with Smad activity drive LPM emergence. We uncover specific activity of zebrafish-derived drl reporters in LPM-corresponding territories of several chordates including chicken, axolotl, lamprey, Ciona, and amphioxus, revealing a universal upstream LPM program. Altogether, our work provides a mechanistic framework for LPM emergence as defined progenitor field, possibly representing an ancient mesodermal cell state that predates the primordial vertebrate embryo.
Keywords: Zebrafish; proteiny dánia pruhovaného; vývojová regulace genové exprese; zesilovače transkripce; Mesoderm; dánio pruhované; intravitální mikroskopie; embryo nesavčí; gastrulace; embryonální indukce; Gastrulation; Embryo, Nonmammalian; mezoderm; zvířata; Animals; Embryonic Induction; Gene Expression Regulation, Developmental; Enhancer Elements, Genetic; Intravital Microscopy; Zebrafish Proteins